2014
DOI: 10.1093/aje/kwu157
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Genitourinary Infections and the Risk of Gastroschisis

Abstract: Genitourinary infections (GUIs) have been associated with increased risk of gastroschisis in 2 studies. Using data collected in the Slone Epidemiology Center Birth Defects Study, we examined the association between GUI and gastroschisis. From 1998 to 2010, mothers of 249 gastroschisis cases and 7,104 controls were interviewed within 6 months of delivery about pregnancy events, including vaginal infections, genital herpes, urinary tract infections (UTIs), and other sexually transmitted diseases (STDs). Women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 41 publications
(39 reference statements)
4
33
3
Order By: Relevance
“…It is unclear whether the medication or the indication for medication is the risk factor in many studies of medication use. A previous study also observed an association between having a urinary tract infection and gastroschisis among younger mothers (Yazdy, Mitchell, & Werler, ) as we did, and another study observed a positive association between having a fever and gastroschisis (Waller et al, ) suggesting that further research into the joint effects of infection, medication use and indication, and maternal age may be warranted.…”
Section: Discussionsupporting
confidence: 83%
“…It is unclear whether the medication or the indication for medication is the risk factor in many studies of medication use. A previous study also observed an association between having a urinary tract infection and gastroschisis among younger mothers (Yazdy, Mitchell, & Werler, ) as we did, and another study observed a positive association between having a fever and gastroschisis (Waller et al, ) suggesting that further research into the joint effects of infection, medication use and indication, and maternal age may be warranted.…”
Section: Discussionsupporting
confidence: 83%
“…While our findings across a number of other factors are in agreement with associations previously reported in the literature-namely with respect to parity [Feldkamp et al, 2008;Duong et al, 2012], education [Jenkins et al, 2014], rural versus urban residence [Salihu et al, 2003], smoking [Siega-Riz et al, 2009;Hackshaw et al, 2011;Khodr et al, 2013;Jenkins et al, 2014], drug abuse [Elliott et al, 2009], maternal nativity [Salemi et al, 2009], and infection [Feldkamp et al, 2008;Elliott et al, 2009;Ahrens et al, 2013;Yazdy et al, 2014]-our findings suggest that these risks may differ somewhat by age grouping. Like others [Salihu et al, 2003;Siega-Riz et al, 2009;Jenkins et al, 2014], before consideration of factors by age grouping, we found that Hispanic women were at increased risk of gastroschisis compared to non-Hispanic white women.…”
Section: Discussioncontrasting
confidence: 83%
“…While others have also observed a relationship between gastroschisis, sexually transmitted diseases, and urinary tract infections [Feldkamp et al, 2008;Elliott et al, 2009;Ahrens et al, 2013;Yazdy et al, 2014], our findings suggest an age-related pattern with respect to the importance of a particular type of infection. Of particular note with respect to age-related patterns is our observation regarding reported infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, some of the 1.3‐fold increased risk appeared to be due to confounding by HSV‐2 infection. Two other studies reported ORs of similar magnitude for self‐reported STDs during the first trimester in relation to gastroschisis although neither of these studies distinguished between specific types of STDs (Feldkamp et al, ; Yazdy et al, ).…”
Section: Discussionmentioning
confidence: 97%